Ionic Liquid and Tween-80 Mixture as an Effective Dispersant for Oil Spills: Toxicity, Biodegradability, and Optimization - Nazar, M. (American Chemical Society, 2022)
Chemical dispersants are used extensively for oil spill remediation. Most of these dispersants are composed of a mixture of surfactants and organic solvents, which raises concerns about aquatic toxicity and environmental impact. In this study, the toxicity and biodegradability of an oil spill dispersant composed of the surface-active ionic liquid 1-butyl-3-methylimidazolium lauroyl sarcosinate BmimLausar and Tween-80 were investigated. In addition, important environmental factors including salinity, temperature, and wave-mixing energy were optimized to obtain maximum dispersion effectiveness. The acute toxicity against zebrafish (Danio rerio) showed that the developed dispersant was practically non-toxic with a median lethal dose of more than 100 mg L-1 after 96 h. The dispersant also demonstrated outstanding biodegradability of 66% after 28 days. A model was developed using a response surface methodology that efficiently (R2 = 0.992) related the salinity, temperature, and wave-mixing energy of seawater to dispersion effectiveness. The system was then optimized, and a high dispersion effectiveness of 89.70% was obtained with an experimental error of less than 2%. Our findings suggest that the surface-active ionic liquid and Tween-80 mixture could be a viable alternative to toxic chemical dispersants for oil spill remediation. Â© 2022 The Authors. Published by American Chemical Society.